CC chemokine receptor 5 (CCR5) mRNA expression in pulmonary sarcoidosis - Petrek, Martin; Gibejova, Agata; Drabek, Jiri; Mrazek, Frantisek; Kolek, Vitezslav; Weigl, Evzen; du Bois, Roland M (Immunology letters, 2002)
The CC chemokine receptor 5 (CCR5) binds the chemokine ligands RANTES (CCL5) and MIP-1alpha (CCL3), which have been implicated in the development of alveolitis in sarcoidosis. We have, therefore, investigated CCR5 mRNA expression in bronchoalveolar lavage fluid (BALF) cells from patients with sarcoidosis. Further, we explored whether there was any association between CCR5 mRNA expression and the presence of the CCR5Delta32 DNA polymorphism. Semiquantitative RT-PCR was used to determine CCR5 mRNA expression from BALF cells from 16 control subjects (C) and 39 patients with sarcoidosis (S). The data on the CCR5Delta32 polymorphism, determined by PCR-SSP, were available for 37 patients. CCR5 mRNA expression was significantly upregulated in sarcoidosis (median+/-SEM, C, 0.00+/-0.07; S, 0.12+/-0.07; P<0.05). When patients were evaluated according to their CCR5Delta32 genotype, an interesting trend emerged with Delta32 positive patients (wt, mt) expressing less mRNA than the patients with both wild-type alleles (wt, wt): 0.00+/-0.09, and 0.26+/-0.09, respectively; P>0.05). In conclusion, upregulation of CCR5 mRNA in BALF of patients with sarcoidosis is consistent with its chemokine ligands RANTES and MIP-1alpha playing a pivotal role in inflammatory cell recruitment to disease sites. Though the data from this pilot study had no clinical correlations we suggest that further studies are warranted on the role of this Th1 subset marker in the pathogenesis of sarcoidosis.
Keywords: Humans; messenger RNA; lidé středního věku; Sarcoidosis, Pulmonary; regulace genové exprese; polymorfismus genetický; Female; Aged; dospělí; polymerázová řetězová reakce s reverzní transkripcí; Bronchoalveolar Lavage Fluid; senioři; lidé; Reverse Transcriptase Polymerase Chain Reaction; Polymorphism, Genetic; Adult; RNA, Messenger; ženské pohlaví; Gene Expression Regulation; Male; Middle Aged; bronchoalveolární lavážní tekutina; Receptors, CCR5; plicní sarkoidóza; mužské pohlaví; receptory CCR5